Phenomenological Study of the Use of the Sekolah.mu Platform in Improving Teacher Pedagogical Competence among MGMB Alumni of Kampus Guru Cikal - Farhin, Nurul; Haryono, Haryono; Budiyono, Budiyono (Journal of Primary Education, 2023)
Education is essential because it can develop and encourage society to become more advanced based on noble values and a noble life to build a good personality. Teachers influence the educational process because they have a position as functional technical practitioners. the relationship between using the Sekolah.mu platform and the pedagogical competence and analyzing the impact of using the Sekolah.mu platform on the pedagogical competence of Kampus Guru Cikal alumni. This research uses a qualitative approach in the form of a phenomenological study using subjective methods. Data collection methods use interview techniques, literature studies, documentation, and FGD. Meanwhile, the data analysis technique uses IPA. The use of the Sekolah.mu platform is related to the pedagogical competence of internship alumni at the Cikal teacher campus. Different alumni backgrounds produce different pedagogical knowledge. They are using the Sekolah.mu application allows alumni from the educational and non-educational fields to collaborate in improving their understanding of pedagogy. This application impacts increasing the pedagogical understanding of Kampus Guru Cikal alumni, accompanied by pedagogical mentoring with mentors. The alumni feel that as educators with this platform, we not only learn but can also share the good practices we have done to inspire people out there.